Prevalence and severity of Depressive illness among youth coming to Psychiatry Out-patient department of District Headquarter Hospital (DHQ), Sargodha - Rida Dawood, Aftab Nazir , Muhammad Shahid Javed , Shoaib Ahmad Malik , Zunera Tanveer , Muhammad Zahid Mustafa, Rida Dawood, Aftab Nazir , Muhammad Shahid Javed , Shoaib Ahmad Malik , Zunera Tanveer , Muhammad Zahid Mustafa (Journal of Rawalpindi Medical College, 2020)
Introduction: Prevalence and severity of depressive illness among the youth are on the rise. Objective: To examine the prevalence and severity of depressive illness among youth coming to the psychiatry outpatient department of District Headquarters Hospital, Sargodha. Material and Methods: This is a descriptive cross-sectional study. The study population includes young people (15-24 years) coming to the Out-patient Department of Psychiatry in District Headquarters Hospital, Sargodha. The duration of the study was from 1st February 2018 to 20th May 2018. 50 patients were selected through the convenience sampling technique. Beck’s depression inventory-II semi-structured questionnaire was used for data collection from people aged 15-24 years coming to psychiatry OPD. The diagnosis was made as per the Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-V). Informed consent was obtained from all participants. Chi-square applied. P-value of 0.05 taken as cut off value. Results: Depression was present in 64% of the study participants. Among female participants, 77.42% of females while among male participants, 42.11% of males were suffering from depression (P-value=0.012) which shows that there is a significant association between gender and depression. Overall, 50% of the participants were mildly depressed, 34.37% were moderately depressed and only 15.63% were severely depressed (P-value = 0.618). Among depressed, 75% were 20-24 years old and 25% were 15-19 years old. Conclusion: Prevalence of depression is found to be more among women and in the young age group 20-24 years. Therefore, regular psychiatric screening, treatment, and follow-up are recommended in an educational institute for early diagnosis and treatment.